2015
DOI: 10.1111/trf.12894
|View full text |Cite
|
Sign up to set email alerts
|

Large animal evaluation of riboflavin and ultraviolet light–treated whole blood transfusion in a diffuse, nonsurgical bleeding porcine model

Abstract: Mirasol-treated FWB did not impact survival, blood loss, tissue oxygen delivery, RBC indices, or coagulation variables in a standardized liver injury model. These data suggest that Mirasol-treated FWB is both safe and efficacious in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Previous observations demonstrated that RBCs treated with Mirasol at higher illumination doses and transfused after 42 days of storage have lower recovery and survival values . Remarkably, transfusion of Mirasol‐treated fresh WB in a porcine model of nonsurgical bleeding did not show significant changes in posttranfusion RBC variables . In vivo survival was further shown to be similar in both untreated and Mirasol‐treated RBCs transfused in baboons; the transfusion of Mirasol‐treated baboon RBCs did not show any evidence of detrimental immune responses .…”
Section: Discussionmentioning
confidence: 74%
“…Previous observations demonstrated that RBCs treated with Mirasol at higher illumination doses and transfused after 42 days of storage have lower recovery and survival values . Remarkably, transfusion of Mirasol‐treated fresh WB in a porcine model of nonsurgical bleeding did not show significant changes in posttranfusion RBC variables . In vivo survival was further shown to be similar in both untreated and Mirasol‐treated RBCs transfused in baboons; the transfusion of Mirasol‐treated baboon RBCs did not show any evidence of detrimental immune responses .…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, this treatment abrogates the ability of contaminating WBC to present the antigen, inhibiting T‐cell proliferation, cytokine production and finally preventing transfusion‐associated graft‐versus‐host disease (ta‐GVHD) . The toxicological safety of WB treated with RF+UV has been demonstrated both in vitro as in animal studies .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Further, a recent animal study has documented in vivo safety and efficacy of treated whole blood. 26 However, RBC damage to pathogen reduced autologous RBCs stored for 42 days has been noted with riboflavin-UV treatment, with a trend toward decreased RBC recovery and survival with increasing UV illumination doses. 25 Of note, recovery of RBCs treated with the current configuration of the Mirasol system for WB at 80 J/mL RBC meets FDA guidelines at 21 days of storage (Terumo BCT, personal communication; manuscript submitted for publication).…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Unlike what has been observed with S‐303, no detrimental nonspecific immune responses have been described to date in studies of riboflavin‐UV light pathogen reduction–treated whole blood . Further, a recent animal study has documented in vivo safety and efficacy of treated whole blood . However, RBC damage to pathogen reduced autologous RBCs stored for 42 days has been noted with riboflavin‐UV treatment, with a trend toward decreased RBC recovery and survival with increasing UV illumination doses .…”
mentioning
confidence: 96%